If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x-7)=-4x+6
We move all terms to the left:
2(3x-7)-(-4x+6)=0
We multiply parentheses
6x-(-4x+6)-14=0
We get rid of parentheses
6x+4x-6-14=0
We add all the numbers together, and all the variables
10x-20=0
We move all terms containing x to the left, all other terms to the right
10x=20
x=20/10
x=2
| −3|1−2/3v|=−9 | | 42=3(2-3b) | | b=85=(10=9) | | 2(4x-2)=22x | | 2x/6=x/2 | | (x-18)=4Y | | −3|1−2/3v|=−9−3|1−2/3v|=−9. | | x^−2−x^−1−72=0 | | -2/7r+2r=1/2r+12/2 | | Z+4.z-4=-23 | | x−2−x−1−72=0 | | 7b−5/2=6b−5/7 | | Y=0.15x+-294.345 | | -3/8x+7=2 | | 35=4d+7 | | 13=4-y | | 2x-6/3=3x+1/2 | | 3x=4=5(x=8) | | 1/3x^2=-3x | | 6-2t/3=2 | | (x-18)=(Y*4) | | (71x-1)+20x=90 | | 4(3x-9=40x | | 30+y/6=371/2 | | 8(4x-1)-12x=11(2x-6)-x | | x2=9 | | 12x=4(x=5) | | x2=9. | | 1/3(4x+5)-2/3=1/9(3x+18) | | 4.z+2.3.z-5=-35 | | 4/x^2+x-20=0 | | 4(3x-9)=40x |